(untitled) (Journal of Biomedical Investigation, 2024)
Background: Malaria remains a major public health problem in sub-Saharan Africa especially among pregnant women and unborn infants. Aim: The effects of malaria infection on the haematological and biochemical parameters of pregnant women were investigated in Onitsha, Anambra State, Nigeria. Materials and Methods: Venous blood samples were collected from 1500 pregnant women who attended antenatal clinic, in Onitsha, Anambra State, Nigeria. The haematological and biochemical parameters of the malaria positive samples were analysed using automated analysers and Giemsa stained blood films. Data was analysed using Chi-square analysis at level of significance of p<0.05. Results: A total of 423 were positive for malaria. Haemoglobin and White blood cell (total and differential) counts were significantly associated with malaria infection (P<0.05). A total of 28 pregnant women (6.6%) who had malaria were found to be anaemic with highest prevalence of anaemia observed: among those less than 20years old (43.3%; p<0.05), in first trimester (20.0%; p<0.05), and among Secundigravidae (7.8%; p<0.05). Case wise, there were 68.3% leucocytosis and 1.4% leucopenia. Decreased platelet count was observed among malaria infected women, with 16(3.8%) having thrombocytosis while 24(5.7%) had thrombocytopenia. The biochemical parameters showed a significant difference between pregnant women with normal values and those with abnormal values (p<0.05). A total of 24(5.7%) of them had elevated ALT, 19(4.5%) had elevated AST, 15(3.6%) had elevated ALP and 32(7.6%) had elevated total bilirubin. Pregnant women less than twenty years old had the highest prevalence 9(30.0%) of elevated ALT, 7(23.3%) of elevated AST, 6(20%) of elevated ALP and 11(36.7%) of elevated total bilirubin. Conclusion: Malaria in pregnancy is a major public health problem affecting women. Pregnant women below 20 years of age are particularly vulnerable to the disease and its associated morbidities including decreased haemoglobin (Hb), platelets counts, full blood counts, resulting in increased risk for anaemia.